"Unutrašnji totalitarizam" umjesto demokracije - Jesmo li osuđeni na distopiju? - Nikodem, Krunoslav (Array, 2004)
The theme of this article is a new socio-political system called "Inner Totalitarianism". The formation of this system is followed through development of science and philosophy. More precisely, it means transition from "black box theory" to theoretical approach that includes an observer as a part of the observing object. The beginning of "Inner Totalitarianism" is placed on boundaries between modern society and its postmodern condition. In this kind of socio-political system, the question of social stability and control moves from the field of power and represion to the field of happiness and entertainment. One of the main thesis of this article, and of a great importance for the understanding of the system typology, is that the process of socialization in the postmodern condition of society, mediated by computer technology and mass media, becomes a process of infatilization. In other words, social acceptable behaviour learning process becomes time reducing process. The notion of time here represents time section from appearance of one's wish to fulfilment of that wish. "Inner Totalitarianism" has essentially dystopian characteristics which mostly appear as a consequence of radically understood liberalism, on the one hand, and some old greed for power, on the other.